Myeloid Disease Mutations of Splicing Factor SRSF2 Cause G2‐M Arrest and Skewed Differentiation of Human Hematopoietic Stem and Progenitor Cells. (27th July 2018) - Bapat, Aditi; Keita, Nakia; Martelly, William; Kang, Paul; Seet, Christopher; Jacobsen, Jeffery R.; Stoilov, Peter; Hu, Chengcheng; Crooks, Gay M.; Sharma, Shalini
Abstract: Myeloid malignancies, including myelodysplastic syndromes, chronic myelomonocytic leukemia, and acute myeloid leukemia, are characterized by abnormal proliferation and differentiation of hematopoietic stem and progenitor cells (HSPCs). Reports on analysis of bone marrow samples from patients have revealed a high incidence of mutations in splicing factors in early stem and progenitor cell clones, but the mechanisms underlying transformation of HSPCs harboring these mutations remain unknown. Using ex vivo cultures of primary human CD34 + cells as a model, we find that mutations in splicing factors SRSF2 and U2AF1 exert distinct effects on proliferation and differentiation of HSPCs. SRSF2 mutations cause a dramatic inhibition of proliferation via a G2‐M phase arrest and induction of apoptosis. U2AF1 mutations, conversely, do not significantly affect proliferation. Mutations in both SRSF2 and U2AF1 cause abnormal differentiation by skewing granulo‐monocytic differentiation toward monocytes but elicit diverse effects on megakaryo‐erythroid differentiation. The SRSF2 mutations skew differentiation toward megakaryocytes whereas U2AF1 mutations cause an increase in the erythroid cell populations. These distinct functional consequences indicate that SRSF2 and U2AF1 mutations have cell context‐specific effects and that the generation of myeloid disease phenotype by mutations in the genes coding these two proteins likely involves different intracellular mechanisms.Stem Cells 2018;36:1663–1675 Abstract : In human hematopoietic stem and progenitor cells, expression of SRSF2 mutations causes a G2‐M arrest and initiation of cytokine induced differentiation triggers apoptosis and skewed myeloid differentiation.